Promotion of early breast milk expression among mothers of preterm infants in the neonatal ICU in an obstetrics and gynaecology hospital: a best practice implementation project. Issue 3 (13th September 2020) - Huang, Xiaoyan; Zhang, Junping; Zhou, Feifei; Yang, Yun; Lizarondo, Lucylynn; McArthur, Alexa
Abstract : Supplemental Digital Content is available in the text ABSTRACT: Introduction: The supply of breast milk to preterm infants is low. It is important to adopt strategies to promote early, frequent and effective expression of breast milk. Objectives: The aim of this best practice implementation project was to promote early breast milk expression among mothers of preterm infants in the neonatal ICU in an obstetrics and gynaecology hospital. Methods: The JBI Practical Application of Clinical Evidence System and Getting Research into Practice audit and feedback tool were used in this project. Questionnaire surveys and interviews were used for baseline and follow-up audits. Results: An overall improvement was observed after the implementation of various strategies. The compliance regarding education provided to healthcare professionals, and mothers after delivery, as well as mothers' access to breast pump increased to 100%. The compliance concerning mothers' education before delivery rose from 0 to 77%. A remarkable increase from 23 to 87% was observed for compliance related to expression of breast milk within 6 h following delivery. The compliance of expression for 8–12 times daily in the first 48 h after delivery also experienced dramatic improvement from 0 to 50%. Conclusion: The current project has demonstrated that the implementation of evidence-based practice was effective in promotion of early breast milk expression among mothers of preterm infants in the neonatal ICU. The role of a nurse specialist in breastfeeding, involvement of multidisciplinary staff and utilization of online networking software were highlighted in this project. Future audits may be undertaken to evaluate the long-term effect of the implementation.